A dynamic test prioritisation based on DU-chain coverage for regression testing. (2018) - Pan, Lili; Wang, Tiane; Qin, Jiaohua; Xiang, Xuyu
Test case prioritisation schedules the test cases for execution in an order that attempts to maximise (an) objective(s) or expose faults earlier in testing. In the past, many test case prioritisation techniques prioritised test cases based on mainly test-requirement coverage and ignored many other testing factors. In view of the DU-chain importance in programs, this paper presents a test case prioritisation approach of method-based DU-chain coverage. The technique combines the DU-chain coverage and fault detection rate as test-case quantitative factors. Different from existing techniques, the novel approach makes use of information from executed testing and module coupling, and dynamically calculates a priority quantitative value for every test case. The experiments performed show that the dynamic prioritisation approach is fault-detection effective, and the APFD of the test suites constructed by the dynamic prioritisation approach is higher than that of the test suites constructed by the static prioritisation technique.